2020
DOI: 10.1088/1361-6528/ab6fdd
|View full text |Cite
|
Sign up to set email alerts
|

Wearable strain sensor based on highly conductive carbon nanotube/polyurethane composite fibers

Abstract: Highly conductive and stretchable fibers have recently attracted increasing attention owing to their potential for application in flexible wearable electronics. Carboxylated carbon nanotubes (c-CNTs) are coated onto flexible fibers as a convenient way of fabricating wearable strain sensors. However, the conductivity of a c-CNT is reduced due to the destruction of the graphitized structure of the CNT during carboxylation. It still remains a significant challenge to endow c-CNT composite fibers with high conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 63 publications
0
20
0
Order By: Relevance
“…The third group has a similar conductance to the molecular wires investigated, ,, revealing that the third group can be used as molecular wires. Based on that, polyurethane composite fibers (PU/CNT@Fe 2+ ) were fabricated by the metal coordination of Fe 2+ ions and carboxylated CNTs . The conductance of PU/CNT@Fe 2+ increased significantly to 72 S/m, which is four times that of PU/CNT fibers without Fe 2+ ions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The third group has a similar conductance to the molecular wires investigated, ,, revealing that the third group can be used as molecular wires. Based on that, polyurethane composite fibers (PU/CNT@Fe 2+ ) were fabricated by the metal coordination of Fe 2+ ions and carboxylated CNTs . The conductance of PU/CNT@Fe 2+ increased significantly to 72 S/m, which is four times that of PU/CNT fibers without Fe 2+ ions.…”
Section: Resultsmentioning
confidence: 99%
“…Incorporation of transition metal ions, especially Fe, Mn, and Ru ions, into the porphyrin framework will result in strong coordination that could enhance the electrical characteristics of electronic materials. In addition, polyurethane (PU) fibers coated with metal ion-linked carboxylated CNTs were fabricated, and we found that metal coordination formed by Fe 2+ ions and carboxyl groups can significantly enhance the conductivity of PU fibers (up to 72 S/m), which is four times that of PU fibers without Fe 2+ ions . We also proved that a strong metal-coordination interaction formed can significantly enhance the conductivity of carbon-based network junctions.…”
Section: Introductionmentioning
confidence: 82%
“…To further achieve high stretchability and wide detection range, strain sensors have been fabricated from elastic polymers, for example, CNT/thermoplastic PU fiber with a multilayer-hollowmonolith structure, 112 PU/CNT@Fe 2+ fibers. 113 By a coating approach, Zhi et al 114 developed a CNT/cotton/PU core-spun yarn strain sensor that is capable of identifying the motions of finger and elbow, and even the eye winking. By virtue of physical interaction between CNT and the cotton/PU yarn, the as-obtained composite yarn can undergo the stretching up to 300% and can be stably operated for a long-term test (ca.…”
Section: Fiber Sensorsmentioning
confidence: 99%
“…However, these strain sensors still exhibit limited stretchability and low strain range. To further achieve high stretchability and wide detection range, strain sensors have been fabricated from elastic polymers, for example, CNT/thermoplastic PU fiber with a multilayer‐hollow‐monolith structure, 112 PU/CNT@Fe 2+ fibers 113 . By a coating approach, Zhi et al 114 .…”
Section: Fiber Electronicsmentioning
confidence: 99%
“…The following supporting information can be downloaded at: https: //www.mdpi.com/article/10.3390/nano12050871/s1, Figure S1: The measurement setup for the PMPF strain sensor; Table S1: The comparison of performance parameters between our strain sensor and other reported fabric-based strain sensors [1,16,21,29,[33][34][35][36][37][38].…”
Section: Supplementary Materialsmentioning
confidence: 99%